Delayed presentation of ectopic pregnancy during the COVID‐19 pandemic: A retrospective study of a collateral effect. Issue 3 (8th March 2021) - Barg, Moshe; Rotem, Reut; Mor, Pnina; Rottenstreich, Misgav; Khatib, Fayez; Grisaru‐Granovsky, Sorina; Armon, Shunit
Abstract: Objective: We aimed to assess the rates of overall diagnosis of ectopic pregnancy (EP), treatment modality and associated complications during the COVID‐19 pandemic compared to the exact time period in the previous year (pre‐COVID‐19). Methods: A retrospective cohort study was conducted at a single referral regional center (Shaare Zedek Medical Center, Jerusalem, Israel). Prevalence of the diagnosis of EP, treatment modality and associated complications during the COVID‐19 lockdown period in the state of Israel (March 10–May 12, 2020) was compared to patients receiving the same diagnosis during the parallel timeframe in the previous year (2019). Results: Overall there were 29 and 43 cases of EP during the COVID‐19 and pre COVID‐19 epoch, respectively. COVID‐19 period patients presented to the emergency room with significantly higher β‐human chorionic gonadotrophin level; median of 1364 versus 633 IU, P  = 0.001. The rate of ruptured EP was; 20.7% versus 4.3% P  = 0.031, and surgical approach; 55.2% versus 27.9%, P  = 0.001. Significantly higher median volume of blood loss; median volume 852 versus 300 ml, P  = 0.042 were observed in patients during the COVID‐19 epoch. Conclusion: The COVID‐19 pandemic led to delayed presentation of patients with EP, and the requirement of subsequent emergency surgical management and excessive blood loss. Special attention should be given to the decline in routine medical care during the pandemic. Synopsis: The COVID‐19 pandemic has led to delayed diagnosis of ectopic pregnancy (EP) and was associated with higher rates of ruptured EP with subsequent emergent surgical management and severe blood loss.